Effect of Dehydroepiandrosterone Sulfate on the Modulation of Memory and Learning in Sprague-Dawley Rat Hippocampus - Shaimi, Asma Ulhusna; Abdullah, Hasmah; Ismail, Zalina; Ahmad, Wan Amir Nizam Wan (Proceeding International Conference on Science and Engineering, 2019)
Dehydroepiandrosterone sulphate (DHEAS) is a neurosteroid that is found in greater concentration within the brain rather than in any other body organ (Corpechot et al., 1981) and studies have shown that in the brain, DHEAS has a role in enhancing both learning and memory (Markowski et.al., 2001). This present study investigated the relationship between DHEAS and spatial learning and memory in the rat hippocampus. Male Sprague-Dawley rats were divided into two groups and their spatial learning behaviour was evaluated with the Morris Water Maze. The intensity of DHEAS was simultaneously recorded in real time via the Fiber Fluorescence Microscopy (FFM) S-650 probe of the Cellvisio system. There were significant changes in the swimming pattern of the experimental groups obtained via the Morris Water Maze from day 1 until day 5 and day 6 for the probe test. Meanwhile, it was also seen that the intensity of DHEAS fluorescence increased in parallel to the swimming pattern of the experimental rats in comparison to the control group. The findings suggest that the changes in DHEAS fluorescence has a strong link to both spatial learning and memory.